Optical and Electrical Properties of Nanocrystalline SnO2 Thin Films Synthesized by Chemical Bath Deposition Method - Sagadevan, Suresh; Podder, Jiban (Scientific Research, 2015)
The chemical bath deposition (CBD) technique was used for the synthesis of the tin oxide (SnO2) thin films. X-ray diffraction (XRD) was employed to find the crystallite size by using Debye Scherrer’s formula. The surface morphology of SnO2 films was analyzed by the scanning electron microscopic (SEM) studies. The FT-IR spectrum exhibits the strong presence of SnO2. The optical properties of the SnO2 thin films were determined using UV-Visible spectrum. The dielectric studies were carried out at different frequencies and at different temperatures for the prepared SnO2 thin films. Further, electronic properties, such as valence electron plasma energy, average energy gap or Penn gap, Fermi energy and electronic polarizability of the SnO2 thin films, were determined. The ac conductivity of the SnO2 thin films increases with increase in temperature and frequency. The activation energy was determined by using dc electrical conductivity measurement. The Hall properties were also calculated.
Keywords: SnO2; CBD; XRD; SEM; FTIR; Dielectric Studies